News reports on research in Swedish newspapers 2002-2013 - Andersson, Ulrika (University of Gothenburg, 2015)
The study examines Swedish news media's reporting on scientific research during the years of 2002-2013 and whether, as well as how, this reporting has changed over time. This has been done by conducting a quantitative content analysis of all articles, editorials and news items on scientific research during the period September 1st-30th 2002-2013, in the major Swedish news media: Dagens Nyheter, Svenska Dagbladet, Göteborgs-Posten, Sydsvenskan and Aftonbladet.

Purpose:

The study examines Swedish news media's general reporting on scientific research during the years of 2002-2013.

Studien undersöker svensk dagspress allmänna rapportering om vetenskaplig forskning under åren 2002-2013 samt om, och i så fall hur, rapporteringen har förändrats över tid. Studien baseras på en systematisk, kvantitativ innehållsanalys av samtliga nyhetsartiklar, analyser, ledarartiklar respektive debattartiklar om vetenskaplig forskning under perioden 1-30 september 2002-2013 i de största svenska dagstidningarna: Dagens Nyheter, Svenska Dagbladet, Göteborgs-Posten, Sydsvenskan samt Aftonbladet.

Syfte:

Studien undersöker svensk dagspress allmänna rapportering om vetenskaplig forskning under åren 2002-2013.
Forskningsrapportering i svensk dagspress 2002-2013
Keywords: mass media; massmedia; mass media exposure; massmediaexponering; news; nyheter; research; forskning; research and development; forskning och utveckling; mass media bias; mediavinkling; press; press; daily press; dagspress; Media; Media; SCIENCE AND TECHNOLOGY; VETENSKAP OCH TEKNOLOGI; Social Sciences; Samhällsvetenskap; Media and Communications; Medie-, kommunikations-, och informationsvetenskaper